PENERAPAN DATA MINING UNTUK PREDIKSI PENJUALAN SPANDUK MENGGUNAKAN ALGORITMA C4.5 - Triawan, Bagus; Lubis, Imran; Kadim, Lina Arliana Nur (Journal of Mathematics and Technology (MATECH), 2024)
Selling banners is an essential part of the advertising business, and having the ability to predict sales can assist companies in more effective production and marketing planning. In this research, we collected banner sales data from January to June 2023 and used the C4.5 algorithm to process the data. The decision tree method can help address issues occurring in the store. RapidMiner will aid in determining which products are more popular and less popular. Using the RapidMiner method will yield more accurate decision data and simplify product analysis. Based on the research findings, banners frequently ordered by consumers. The results of this research can serve as a guide for companies to optimize their banner sales strategies.